Elaborately manufacturing an electrochemical aptasensor based on gold nanoparticle/COF composites for amplified detection performance - Zhu, Qian-Qian; Zhang, Wen-Wen; Zhang, Han-Wen; Yuan, Rongrong; He, Hongming (Journal of materials chemistry. C, Materials for optical and electronic devices, 2020)
Gold (Au) nanoparticle-embedded covalent organic frameworks (namely Au@COFs) were ingeniously designed and prepared by using a straightforward impregnation-reduction method. This composite not only owns outstanding stability, rich π functional sites, superior electroconductibility, high surface area, and well-ordered porous structures, but also possesses relatively strong non-covalent affinity toward aptamers, synergistically resulting in the establishment of highly efficient electrochemical aptasensors for detecting analytes. Ciprofloxacin (CIP), for instance, is selected and investigated as a research model to estimate the feasibility and superiority of Au@COF-based aptasensors. The as-made Au@COF-based aptasensor exhibits awesome sensing performance with the lowest limit of detection of 2.34 fg mL −1 (7.06 fM) in a concentration range from 1.0 × 10 −5 to 0.5 ng mL −1 as determined by analyzing electrochemical impedance signals, which is approximately attributed to numerous aptamer strands on the surface of COFs via strong π-π stacking interaction and the contribution of electrical conductivity from trapped Au nanoparticles. Concurrently, the fabricated aptasensor reveals excellent repeatability, circularity, selectivity, and stability as well as precise detection capability in a variety of real samples. This strategy provides a workable concept for developing and synthesizing of metal nanoparticle-built-in COF composites and their aptasensors in the extended electrochemical detection field. An electrochemical aptasensor based on Au@COF is designed and fabricated with excellent electrochemical detection performance.